2013
DOI: 10.1007/s10934-013-9761-8
|View full text |Cite
|
Sign up to set email alerts
|

Pore size dependence of self-assembled type photonic crystal on dye-sensitized solar cells efficiency utilising Chlorine e6

Abstract: There are few reports on photoelectric conversion efficiency using naturally-occurring dyes for dyesensitized solar cells (DSSC). This is because the matching with an excited electronic level of naturally-occurring dye to the conduction band of semiconductor is problematic; the excited electrons are easily relaxed to the steady state with fluorescence or heat emission. We examined the fluorescence inhibition effect of a self-assembled photonic crystal using Chlorine e6 dye. Chlorine e6 is derived from chloroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…3j. 25 Obviously, the large resistances of our system indicated that the electrolyte intrusion into the inverse opals were not enough.…”
Section: Electrochemical Impedance Analysismentioning
confidence: 89%
See 2 more Smart Citations
“…3j. 25 Obviously, the large resistances of our system indicated that the electrolyte intrusion into the inverse opals were not enough.…”
Section: Electrochemical Impedance Analysismentioning
confidence: 89%
“…could be fabricated using LPD method on polystyrene colloidal crystals. 25 Here the author should mention that these inverse opals can show anomalous group velocity but no complete photonic bandgap.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[102,103] A lower Warburg impedance of the gel electrolyte also contributes to the PCE enhancement of an IO PC coupled device. [102] This study offers new strategy and new insight to the coupling of PC to a solar cell for light management. rise to higher fill factor (FF) and PEC than those of smaller pores with larger surface area, which showed the difference, as described above, between QDSSCs and DSSCs.…”
Section: Application Of Pcs In Sensitized Solar Cellsmentioning
confidence: 99%
“…It was proposed that the optimized PC structure should has its stop band matched with the absorption peak of the dye. 41 Modified TiO 2 IO structures, including TiO 2 quasi-IO 60 and mesoporous IO PC films, 102 were also fabricated to improve the scattering effect and the surface area of the PC films. By coupling the TiO 2 quasi-IO layer, the PCE was increased from 3.0% to 5.7% for an B4.1 mm thick TiO 2 NP layer and from 4.0% to 6.1% for an B10 mm thick TiO 2 NP layer.…”
Section: Liquid-state Dsscsmentioning
confidence: 99%